Kajian Etnofarmasi Kelompok Masyarakat Banjar Saraseda Tampaksiring Gianyar Bali - Puspita Wati, Ni Putu; Anita Dewi, Ni Luh Kade Arman; Suradnyana, I Gede Made; Kusuma Yuda, I Putu Era Sandhi; Cahyaningsih, Erna; Megawati, Fitria (Usadha, 2023)
The use of ethnopharmaceutical practices remains widespread in Bali, as this knowledge has been passed down through generations. Although the Balinese people still strongly uphold their traditional healing systems and have long utilized plants as medicinal ingredients, there is still limited research documenting the diversity of plant species recorded in the Usadha manuscripts along with their therapeutic uses. This study aimed to inventory medicinal plants that are still used by the community in Banjar Saraseda, Tampaksiring, Gianyar, Bali. The study employed a descriptive design, with data collected through interviews to obtain information from respondents regarding local plant names, therapeutic uses/indications, parts of the plant utilized, and methods of preparation and application. The data were analyzed descriptively and presented in tables. Based on the ethnopharmacological survey conducted in Banjar Saraseda, Tampaksiring, Gianyar, Bali, a total of 20 medicinal plant species were recorded. The most frequently used plant parts were leaves (75%), followed by rhizomes (15%) and fruits (10%). The primary methods of preparation included boiling (65%), pounding (15%), grating, crushing, brewing, and direct use (each 5%). Based on therapeutic indications, the plants were mainly used to treat fever (20%), muscle pain and gout (20%), hypertension (20%), skin itching (10%), diabetes (10%), and to manage wounds, diarrhoea, haemorrhoids, and gastritis (each 5%). This study demonstrates that the Banjar Saraseda community in Tampaksiring, Gianyar, Bali continues to preserve traditional knowledge in the use of medicinal plants that has been inherited through generations.